2007
DOI: 10.1017/s0033291707001845
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic-like experiences and other antecedents of schizophrenia in children aged 9–12 years: a comparison of ethnic and migrant groups in the United Kingdom

Abstract: African-Caribbean children, as compared to white British children, experienced greater risk on all four indices. There were trends for South Asian and Oriental children to present lowered risk on several indices, relative to white British children. Migration status was unrelated to any risk index. ConclusionPrevalence of the putative antecedents of schizophrenia is greater among children of African-Caribbean origin living in the UK than among white British children. This parallels the increased incidence of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 19 publications
3
49
0
Order By: Relevance
“…Baseline (BL) data were collected between 2005 and 2010 in 73 primary schools within Greater London, the procedure for which has been described previously in detail (Laurens et al, 2007(Laurens et al, , 2008(Laurens et al, , 2012. In brief, 8099 children (50% male) aged 9-11 years (mean 10.4 years, sd 0.8 years) completed questionnaires in class, with corresponding questionnaires completed by the child's primary caregiver at home and returned via reply-paid mail.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline (BL) data were collected between 2005 and 2010 in 73 primary schools within Greater London, the procedure for which has been described previously in detail (Laurens et al, 2007(Laurens et al, , 2008(Laurens et al, , 2012. In brief, 8099 children (50% male) aged 9-11 years (mean 10.4 years, sd 0.8 years) completed questionnaires in class, with corresponding questionnaires completed by the child's primary caregiver at home and returned via reply-paid mail.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was drawn predominantly from deprived inner-city London (Laurens et al, 2007(Laurens et al, , 2008(Laurens et al, , 2012 and exceeds the prevalence of PLEs described in other pre-adolescent samples (range 6-17%, Poulton et al, 2000;Polanczyk et al, 2010;Wigman et al, 2011b). This elevated prevalence may relate to the demographics of this sample: the residing adult community has an elevated incidence of schizophrenia (Kirkbride et al, 2006) in addition to a self-reported PLE prevalence of 20% (Morgan et al, 2009).…”
Section: Prevalence Of Plesmentioning
confidence: 97%
“…Validation is important because translation can result in difference in item meaning, and different cultures may have different manifestations of PP. A late adolescent population was chosen since young people are at the highest risk to display PLEs (Laurens et al, 2008;Poulton et al, 2000), and to transition to a psychotic disorder (Harrop and Trower, 2001). By validating CAPE-C in adolescents and young adults, we hope to recast this aperture of vulnerability into a window of opportunity for early detection and intervention.…”
Section: Introductionmentioning
confidence: 99%
“…A similar relationship was subsequently reported by Welham et al (2009) between auditory hallucinations reported by 14-year-olds and the presence of a psychotic disorder at 21 years of age. A large body of research has now accumulated indicating that these early psychotic phenomena also have etiological features in common with clinically relevant psychotic disorders (Laurens et al 2008;Polanczyk et al 2010). Therefore, a strong case has been made for these more prevalent psychotic symptoms to be used in longitudinal research designs as a subclinical phenotype to provide further insights into the origins of schizophrenia (Kelleher & Cannon, 2011), in addition to forming a target for preventive interventions (Morrison et al 2004).…”
Section: Introductionmentioning
confidence: 99%